The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/htj.21301
|View full text |Cite
|
Sign up to set email alerts
|

Multiobjective thermo‐economic and thermodynamics optimization of a plate–fin heat exchanger

Abstract: In the present work, a multiobjective heat transfer search (MOHTS) algorithm is proposed and investigated for thermo‐economic and thermodynamic optimization of a plate–fin heat exchanger (PFHX). Heat exchanger effectiveness and total annual cost (TAC) are considered as thermo‐economic objective functions. Similarly, entropy generation rate and heat exchanger effectiveness are considered as thermodynamic objective functions. Six design variables including flow length of cold and hot streams, no flow length, fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…These noticeable advantages of the HTS algorithm are observed at the cost of computation time. HTS has been successfully applied to different benchmarking problems pertaining to different fields [27,28,29,30,31]. However, to the best of the authors’ knowledge, no study has been reported on the application of HTS for manufacturing problems.…”
Section: Introductionmentioning
confidence: 99%
“…These noticeable advantages of the HTS algorithm are observed at the cost of computation time. HTS has been successfully applied to different benchmarking problems pertaining to different fields [27,28,29,30,31]. However, to the best of the authors’ knowledge, no study has been reported on the application of HTS for manufacturing problems.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed pseudocode of the HTS algorithm is given in Figure . Few application of HTS algorithm for the optimization of engineering system are available in the literature …”
Section: Hts Algorithmmentioning
confidence: 99%
“…The MOHTS algorithm uses Ɛ ‐dominance based updating method to check the domination of the solution in the archive. Extended details about MOHTS algorithm is documented in the references …”
Section: Heat Transfer Search (Hts) Algorithmmentioning
confidence: 99%